2019
DOI: 10.1093/biolre/ioz074
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of prostaglandin F2α metabolite in dairy cattle during luteal regression and pregnancy: implications for corpus luteum maintenance†

Abstract: Mechanisms of bovine corpus luteum (CL) maintenance during the second month of pregnancy have not been adequately investigated, despite significant reproductive losses. In the first month, interferon-tau is believed to suppress oxytocin-stimulated prostaglandin F2α (PGF) production, yet there are conflicting reports of circulating PGF metabolite (PGFM). In this study, characterization of PGFM and P4 occurred through continuous bihourly blood sampling in cows undergoing CL regression (day 18–21, n = 5), and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 68 publications
2
10
0
1
Order By: Relevance
“…On the one hand, pregnant ruminants were reported to have higher concentrations of basal PGF2A than cyclic animals have [ 47 , 48 ]. However, recent publications have suggested that although the numbers of PGF2A pulses per day were significantly higher during luteolysis, compared with pregnant animals, they were similar in the pregnant animals and in those at the late luteal phase [ 40 , 49 ]. Additionally, PGF2A can reach the CL during early pregnancy as shown by Banu and coworkers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, pregnant ruminants were reported to have higher concentrations of basal PGF2A than cyclic animals have [ 47 , 48 ]. However, recent publications have suggested that although the numbers of PGF2A pulses per day were significantly higher during luteolysis, compared with pregnant animals, they were similar in the pregnant animals and in those at the late luteal phase [ 40 , 49 ]. Additionally, PGF2A can reach the CL during early pregnancy as shown by Banu and coworkers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…All cows were housed in a tiestall barn, fed a standard herd diet, and milked twice daily. On d 6, all cows were fitted with an indwelling jugular catheter as described elsewhere (Mezera et al, 2019) and randomized to 1 of 2 treatments on the morning of d 7 after collection of baseline blood samples 24, 2, 1, and 0 h before treatment. Cows were randomized to the following 2 treatments: (1) 25 mg (2 mL) of dinoprost tromethamine (Lutalyse HighCon; Zoetis) adminis-Effect of route of administration of dinoprost tromethamine on plasma profiles of 13,14-dihydro-15-keto-prostaglandin F 2α and progesterone in lactating Holstein cows M. A. Mezera, 1,2 M. R. Lauber, 1 A. D. Beard, 1,2 E. M. Cabrera, 1 M. C. Wiltbank, 1 and P. M. Fricke 1 * tered intramuscularly in the semitendinosus muscle (IM; n = 6), or (2) administered subcutaneously in the neck contralateral to the jugular catheter (SC; n = 6).…”
Section: Short Communication Physiologymentioning
confidence: 99%
“…Concentrations of PGFM were evaluated using an ELISA based on the method reported by Ginther et al (2010) with minor modifications reported by Mezera et al (2019). The intra-and interassay coefficients of variation (CV) were 8 and 14%, respectively, and sensitivity was 5.2 pg/mL.…”
Section: Short Communication Physiologymentioning
confidence: 99%
“…Multiparous Holstein cows were housed in a tiestall barn, milked twice per day, and fed a standard herd diet. As previously described (Mezera et al, 2019), 32 cows were synchronized, with half bred and half uninseminated. Blood was collected from the jugular vein on d 18 to 21 to analyze circulating progesterone (P4) and PGF 2α metabolite (PGFM) to determine regression status, while biopsies were collected daily from d 18 to 21 with a transvaginal guided ultrasound probe, as described and validated by Tsai et al (2001).…”
Section: Animals Experimental Design Sample Collection and Animal Classificationmentioning
confidence: 99%